A one-step facile synthesis of Ag–Ni core–shell nanoparticles in water-in-oil microemulsions - Xia, Lixin; Hu, Xinhu; Kang, Xiaobo; Zhao, Hongping; Sun, Mengtao; Cihen, Xiaowei (Colloids and surfaces. A, Physicochemical and engineering aspects, 2010)
A one-step facile synthesis is devised for preparation of well-dispersed Ag–Ni core–shell nanoparticles with uniform and intact shells. The process is performed by a reduction of silver nitrate and nickel nitrate with sodium borohydride in water-in-oil (W/O) microemulsions of water/polyoxyethylene (4) nonylphenol (OP-4) and polyoxyethylene (7) nonylphenol (OP-7)/ n-heptane. Transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and UV–vis absorption are utilized to characterize the Ag–Ni core–shell nanoparticles. Furthermore, the effect of molar ratio of Ni 2+ to Ag + and dosage of Ni 2+ and Ag + on morphology of the core–shell nanostructure is also discussed in detail. The thickness of Ni layers on the surface of Ag nanoparticles could be controlled by the dosage of Ni 2+ and Ag +. The Ag–Ni core–shell nanoparticles showed a high catalytic activity for degradation reaction of eosin Y. The product may also have many potential applications in optical, magnetic, biochemical, and biomedical fields. The synthetic method reported here suggests a very promising route for the preparation of bimetallic core–shell structures, which is a subject of intense interest.